2013
DOI: 10.1002/bdra.23093
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin A intake below the recommended daily intake during pregnancy and the risk of congenital diaphragmatic hernia in the offspring

Abstract: BACKGROUND: Vitamin A has been related to the etiology of congenital diaphragmatic hernia (CDH). We performed a case-control study to investigate whether maternal dietary vitamin A intake is related to CDH in the offspring. METHODS: Thirty-one pregnancies diagnosed with CDH and 46 control pregnancies were included during the study. After CDH diagnosis and inclusion of controls by risk set sampling, maternal vitamin A intake was investigated with a food frequency questionnaire. Serum retinol and retinol-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…Participants with missing values for these confounders were excluded from the adjusted analysis. According to the findings from the earlier study (12) , we examined this association among mothers with adequate weight (18•5 ≤ prepregnancy BMI < 25•0 kg/m 2 ). To verify the robustness of the observed association, further sensitivity analyses were conducted as follows: (1) further adjusting for socioeconomic status, including educational background, household income and occupation in early pregnancy; (2) excluding users of multi-vitamin supplements in early pregnancy or mothers with severe morning sickness to avoid the misclassification of vitamin A intake; (3) restricting to isolated CDH cases, because complicated CDH might be different from isolated CDH in aetiology and (4) further adjusting for dietary intake of folate and vitamin C, which are similar to dietary sources of vitamin A, and use of folic acid supplement, or for total vitamin A intake in mid-late pregnancy, to explore the possibility of the independent association between vitamin A intake in early pregnancy and CDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with missing values for these confounders were excluded from the adjusted analysis. According to the findings from the earlier study (12) , we examined this association among mothers with adequate weight (18•5 ≤ prepregnancy BMI < 25•0 kg/m 2 ). To verify the robustness of the observed association, further sensitivity analyses were conducted as follows: (1) further adjusting for socioeconomic status, including educational background, household income and occupation in early pregnancy; (2) excluding users of multi-vitamin supplements in early pregnancy or mothers with severe morning sickness to avoid the misclassification of vitamin A intake; (3) restricting to isolated CDH cases, because complicated CDH might be different from isolated CDH in aetiology and (4) further adjusting for dietary intake of folate and vitamin C, which are similar to dietary sources of vitamin A, and use of folic acid supplement, or for total vitamin A intake in mid-late pregnancy, to explore the possibility of the independent association between vitamin A intake in early pregnancy and CDH.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, low vitamin A intake increased the risk of CDH among women who used vitamin supplements periconceptionally (11) . Also, in the Netherlands, adequate-weight mothers who delivered infants with CDH showed a lower vitamin A intake than control mothers (12) . However, these were both case-control studies.…”
mentioning
confidence: 95%
“…In others, higher intakes of thiamin; riboflavin; vitamins B6, C, and E; niacin; and retinol were associated with decreased risk of spina bifida (Chandler et al 2012). Vitamin A deficiency during pregnancy has also been associated with congenital diaphragmatic hernia (Beurskens et al 2013).…”
Section: Birth Defectsmentioning
confidence: 98%
“…Animal studies showed increased contractility and impairment in endothelium-dependent relaxation of pulmonary arteries in nitrofen-exposed animals (Luong et al 2011 ). Moreover, nitrofen generates a perturbation in the retoinid pathway (Thébaud et al 1999 ), that may be, at in least in part, responsible for typical CDH phenotype in humans (Beurskens et al 2010(Beurskens et al , 2013 .…”
Section: Experimental Cdhmentioning
confidence: 99%